Nitrogen and Metal Ions Accumulation in Two Sensitive Himalayan Lichens From Western Nepal: A Reference for Ecosystem Health Monitoring - Suman Prakash Pradhan; Hirendra Bista; Bishal Lamsal; Nirvik Dotel; Bishnu Prasad Pandey; Subodh Sharma (Journal of Chemistry)
In this study, thalli nitrogen (N) and metal ions contents in the two fruticose lichens (Ramalina intermedia and Usnea cornuta) were quantified, which were collected from a pristine Himalayan forest of Shey Phoksundo National Park of western Nepal. Besides, the probable impacts of N and metal ions in physicochemical responses such as electrical conductivity, chlorophyll contents, and chlorophyll degradation were studied. Our initial hypothesis was there are considerable amounts of thallus N and metal ions in lichens from the study area, and it has substantial impacts on physicochemical responses. In comparison, the thalli N concentration was observed to be the greatest in R. intermedia thalli (0.24%–1.15%). However, comparable amounts of metal ions in both lichen species were observed. Regression analysis revealed the least or no impacts of N and metal ions in physicochemical responses. The principal component analysis suggests the contribution of different environmental variable and their correlation with lichen’s variables. This study provides evidence of the least concentration of N and metal ions and only minor impacts on the physicochemical integrity of the two sensitive lichens in our study area. This study is likely to contribute as field-based reference information for further studies on the species-specific N and metal ions accumulation in lichens from different Himalayan forest systems to monitor ecosystem health.